Digital finance, environmental regulation, and green development efficiency of China - Han, Yaqing; Li, Yushui; Wang, Qiangqiang (Frontiers in Environmental Science, 2023)
In the context of the increasingly prominent contradiction between economic development and ecological environment, how to promote green development has become the core of sustainable economic development. Digital finance, as an innovative financial model with a high degree of integration of finance and digital technology, provides a new opportunity for achieving green development. Based on identifying the mechanisms of digital finance and environmental regulation on green development efficiency, this paper uses the directional distance function and Malmquist-Luenberger index to measure the green development efficiency of 30 Chinese provinces from 2011 to 2020, and then uses a dynamic panel GMM model to empirically analyze the relationship between digital finance, environmental regulation and green development efficiency. The results of the study show that (1) Digital finance contributes to the efficiency improvement of green development. (2) Environmental regulation has not yet crossed the "Porter's inflection point" and still has a dampening effect on the efficiency of green development. (3) The synergy between digital finance and environmental regulation has a positive impact on green development. Digital finance can alleviate the financing constraints arising from environmental regulation, and to some extent weaken the negative effect of environmental regulation on the efficiency of green development. In view of this, the government should give full play to the active role of digital finance in eco-environmental governance, optimize the top-level design of environmental regulation, and promote industrial structure upgrading and optimal allocation of financial resources.